Species Composition,Abundance And Distribution Of Jellyfish In The Coastal Waters Of Penang National Park And Manjung - Chuah , Chern Chung (2012)
A study of species composition, abundance and distribution of jellyfish population in the Straits of Malacca, Malaysia, was conducted for 14-months around the coastal waters of Penang National Park (PNP), Penang (November, 2009 to December, 2010) and Manjung, Perak (September, 2009 to October, 2010). Towing and scooping methods were used for sample collection using a fishing boat cruising at the speed of approximately 2.5 nautical knots during neap tide. The scooping method used visual observation to detect jellyfish on the water surface. Meanwhile towing method required a custom-made trawl towed behind the boat for submerged jellyfish sample. A total number of 5 jellyfish species from 5 genera were identified,